Out of pocket expenditure and distress financing on cesarean delivery in India: evidence from NFHS-5 - Rajeev Ranjan Singh; Anjali Sharma; Sanjay K. Mohanty (BMC Health Services Research, 2023)
Abstract Background Though over three-fourths of all births receive medical attention in India, the rate of cesarean delivery (22%) is twice higher than the WHO recommended level. Cesarean deliveries entail high costs and may lead to financial catastrophe for households. This paper examines the out-of-pocket expenditure (OOPE) and distress financing of cesarean deliveries in India. Methods We used data from the latest round of the National Family Health Survey conducted during 2019–21. The survey covered 636,699 households, and 724,115 women in the age group 15–49 years. We have used 159,643 births those delivered three years preceding the survey for whom the question on cost was canvassed. Descriptive analysis, bivariate analysis, concentration index (CI), and concentration curve (CC) were used in the analysis. Result Cesarean deliveries in India was estimated at 14.08%, in private health centres and 9.96%  in public health centres. The prevalence of cesarean delivery increases with age, educational attainment, wealth quintile, BMI and high for those who had pregnancy complications, and previous birth as cesarean. The OOPE on cesarean births was US$133. It was US$498 in private health centres and US$99 in public health centres. The extent of distress financing of any cesarean delivery was 15.37%; 27% for those who delivered in private health centres compared to 16.61% for those who delivered in public health centres. The odds of financial distress arising due to OOPE on cesarean delivery increased with the increase of OOPE [AOR:10.00, 95% CI, 9.35–10.70]. Distress financing increased with birth order and was higher among those with low education and those who belonged to lower socioeconomic strata. Conclusion High OOPE on a cesarean delivery leads to distress financing in India. Timely monitoring of pregnancy and providing comprehensive pregnancy care, improving the quality of primary health centres to conduct cesarean deliveries, and regulating private health centres may reduce the high OOPE and financial distress due to cesarean deliveries in India.